Simple approach to bacterial genomes comparison based on Average Nucleotide Identity (ANI) using fastANI and ANIclustermap - Musiał, Klaudia; Petruńko, Leon; Gmiter, Dawid (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
The Average Nucleotide Identity (ANI) was proposed as a standard for taxonomic affiliation of newly sequenced bacterial genomes. However, usage of ANI value as a means of strains phenotypic diversity offers a relatively easy way for studding bacterial phylogeny. Here we present a simple approach to bacterial genomes comparison based on ANI using fastANI and ANIclustermap. Both programs are available as an open-source tools and can be run using simple command lines. We present protocol for programs installation as a conda packages, that facilitate it utilization. Further, we explain how to prepare commands to perform the analysis. We believed our work could be useful for young scientist that begin their experience with bioinformatics.